Effect of ‘Azotobacter’ and ‘Phosphotika’ biofertilizers on the spawn-run, pinning and yield of the white button mushroom (Agaricus bisporus) - Ahlawat, O P; Rai, R D (Mushroom Research, 2015)
Please see the full text